Adaptive Model Predictive Control for Yaw System of Variable-speed Wind Turbines - Dongran Song; Qing Chang; Songyue Zheng; Sheng Yang; Jian Yang; Young Hoon Joo (Journal of Modern Power Systems and Clean Energy, 2021)
Due to varying characteristics of the wind condition, the performance of the wind turbines can be optimized by adapting the parameters of the control system. In this letter, an adaptive technique is proposed for the novel model predictive control (MPC) for the yaw system of the wind turbines. The control horizon is adapted to the one with the best predictive performance among multiple control horizons. The adaptive MPC is demonstrated by simulations using real wind data, and its performance is compared with the baseline MPC at fixed control horizon. Results show that the adaptive MPC provides better comprehensive performance than the baseline ones at different preview time of wind directions. Therefore, the proposed adaptive technique is potentially useful for the wind turbines in the future.